2018
DOI: 10.1097/sap.0000000000001363
|View full text |Cite
|
Sign up to set email alerts
|

Use of FLIR ONE Smartphone Thermography in Burn Wound Assessment

Abstract: There is a strong correlation between FLIR ONE and ICG when assessing salvageable tissue in third-degree burn wounds. FLIR ONE maximizes the convenience and cost-effectiveness of infrared thermography technology but may overestimate unsalvageable tissue area. FLIR ONE is promising as an adjunct to current imaging modalities such as ICG but requires further study for comparison.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 19 publications
0
33
0
8
Order By: Relevance
“…The skin is a functional organ acting on temperature control. Increased local skin temperature indicates augment of blood perfusion or vascularization, which can reflect changes in metabolic activity or inflammation [13,14]. An increase in temperature is emitted as infrared radiation, which can be measured by infrared thermal imager, such as FLIR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The skin is a functional organ acting on temperature control. Increased local skin temperature indicates augment of blood perfusion or vascularization, which can reflect changes in metabolic activity or inflammation [13,14]. An increase in temperature is emitted as infrared radiation, which can be measured by infrared thermal imager, such as FLIR.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of highresolution digitalized images and image analysis system, it is more sensitive to temperature changes at 0.08 C and has a high sensitivity of 100% in detecting malignant tumors without direct contact with patient. Recently, more and more studies have focused on another application area, such as the assessment of breast reconstruction, severe hidradenitis suppurativa, burn wound and glucocorticoid-induced obesity [13,[16][17][18][19]. Positive conclusions are obtained in most studies.…”
Section: Discussionmentioning
confidence: 99%
“…W transplantologii opisywane jest zastosowanie badań termowizyjnych do oceny czasu tzw. zimnego niedokrwienia podczas operacji chirurgicznych przeszczepiania nerki [16], w chirurgii do oceny rozległości oparzeń [17] oraz konieczności wykonania przeszczepu skóry po oparzeniu termicznym [18]. Termowizja ma również zastosowanie w medycynie sądowej w celu określenia czasu zgonu, wykorzystując zjawisko pośmiertnego schładzania się zwłok [19].…”
Section: Zastosowanie Termografii W Medycynieunclassified
“…Recently, small, low‐priced, handheld thermal imagers became available. These thermal imagers can produce easy and fast measurements attached to a mobile device or tablet . Earlier work from our study group showed that one of these feasible thermal imagers had an excellent reliability (intraclass correlation coefficient: 0.99, standard error of measurement: 0.20°C), but a moderate validity (area under the curve of 0.69) for measuring burn wound healing potential, when compared to the observed healing time.…”
Section: Introductionmentioning
confidence: 99%